2021
DOI: 10.1177/0267659120987545
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic predictors of exercise induced pulmonary hypertension in patients with asymptomatic moderate to severe mitral regurgitation and preserved left ventricular ejection fraction

Abstract: Background: The significant role of mitral regurgitation (MR) in development of pulmonary hypertension (PH) has been proved in previous studies. Experts suggest systolic pulmonary arterial pressure (SPAP) ⩾60 mmHg during exercise as a significant threshold of negative prognostic value in patients with MR. Purpose: The aim of this study was to evaluate the changes of SPAP and to ascertain the determinants of exercise induced pulmonary hypertension (EIPH) in patients with asymptomatic primary MR. Methods: We per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…However, this indication was removed in 2014 due to a lack of evidence [ 58 ]. Žvirblytė R et al, suggested that the elevation of PASP ≥ 60 mmHg during ESE can unmask symptoms and subclinical LV dysfunction in otherwise-called “asymptomatic” patients [ 74 , 75 ]. It seems that EIPH is common in patients with primary moderate to severe MR and preserved LVEF, and its presence is associated with resting LV diastolic dysfunction [ 76 ], as well as an increased risk of adverse cardiac events following MVR [ 70 ].…”
Section: Left Ventricle Valvular Diseases and Pulmonary Hypertensionmentioning
confidence: 99%
“…However, this indication was removed in 2014 due to a lack of evidence [ 58 ]. Žvirblytė R et al, suggested that the elevation of PASP ≥ 60 mmHg during ESE can unmask symptoms and subclinical LV dysfunction in otherwise-called “asymptomatic” patients [ 74 , 75 ]. It seems that EIPH is common in patients with primary moderate to severe MR and preserved LVEF, and its presence is associated with resting LV diastolic dysfunction [ 76 ], as well as an increased risk of adverse cardiac events following MVR [ 70 ].…”
Section: Left Ventricle Valvular Diseases and Pulmonary Hypertensionmentioning
confidence: 99%